2003
DOI: 10.1063/1.1594284
|View full text |Cite
|
Sign up to set email alerts
|

Thin film encapsulated flexible organic electroluminescent displays

Abstract: We describe encapsulated passive matrix, video rate organic light-emitting diode (OLED) displays on flexible plastic substrates using a multilayer barrier encapsulation technology. The flexible OLED (FOLED™) displays are based on highly efficient electrophosphorescent OLED (PHOLED™) technology deposited on barrier coated plastic (Flexible Glass™ substrate) and are hermetically sealed with an optically transmissive multilayer barrier coating (Barix™ encapsulation). Preliminary lifetime to half initial luminance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
150
1
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(157 citation statements)
references
References 13 publications
2
150
1
4
Order By: Relevance
“…The above rate law for Cr(III) oxidation (i.e., at the expense of a manganite phase) has been employed primarily in an attempt to most accurately represent the importance of Mn(III) in the process of Cr(III) oxidation (83)(84)(85)(86)(87). In addition, this rate law has been validated over a relatively wide pH range, making it suitable for analysis of generalized soil fluid conditions.…”
Section: The Calculations Shown In Main Textmentioning
confidence: 99%
“…The above rate law for Cr(III) oxidation (i.e., at the expense of a manganite phase) has been employed primarily in an attempt to most accurately represent the importance of Mn(III) in the process of Cr(III) oxidation (83)(84)(85)(86)(87). In addition, this rate law has been validated over a relatively wide pH range, making it suitable for analysis of generalized soil fluid conditions.…”
Section: The Calculations Shown In Main Textmentioning
confidence: 99%
“…Besides lengthy processing, it was also shown that Barix thin-film encapsulation does not acquire the integrity of glass barrier layers for flexible or rigid substrate OLEDs [712]. Therefore, a need exists for alternative means of suppressing dark spots growth -means that would not introduce complexity or potential for cost increase.…”
Section: Recent Os Device Developmentsmentioning
confidence: 99%
“…Another study conducted in this context [712] demonstrated that the use of Barix encapsulation on plastic substrates showed one fourth of the half-life of a glass encapsulated and glass substrate devices. For comparison, Barix encapsulation resulted in 3700 h of half-life for a glass substrate OLED vs. 2500 h for a plastic substrate OLED [712]. This study clarified that even superior commercial thin-film barrier layers did not achieve the highquality encapsulation, which was seen with glass barriers.…”
Section: Recent Os Device Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Major problems when creating organic solar cells and solar cells, used the dyes, is the need to increase the absorption of visible light by layer to increase the sensitivity [22] and photochemical stability of dyes [24]. The most important problem is the durability of the use of organic solar cells [25].…”
Section: Thin-film Silicon Solar Cells On Flexible Substrates Andrey mentioning
confidence: 99%